Composite diaphragm, preparation method thereof, battery and electric device
By using a composite functional layer of modified ceramics and modified sepiolite fibers in the lithium-ion battery separator, the problems of insufficient thermal stability and electrolyte wetting properties of the polyolefin separator are solved, and higher heat resistance and battery cycle stability are achieved.
Patent Information
- Application Number
- CN202510026793.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The thermal stability and electrolyte emollience of existing polyolefin separators lead to the risk of performance degradation during battery charge and discharge cycles and aging.
A composite separator is used, which includes a base film layer and a functionally modified layer. The functional modified layer consists of modified ceramics and modified sepiolite fibers. The ceramic particles are coated with polydopamine, and the sepiolite fibers are coated with silane coupling agent, forming a stable three-dimensional structure through crosslinking agent.
The heat resistance, mechanical strength, peel strength and ionic conductivity of the composite separator are improved, and the cycle stability and electrochemical properties of the battery are significantly enhanced.
Smart Images

Figure BDA0005234295400000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite diaphragm and a preparation method thereof, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in many fields such as portable electronic devices and electric vehicles due to their advantages such as high energy density and long cycle life. As one of the key components of the battery, the separator plays the role of isolating the positive and negative electrodes and providing microporous channels for ion transmission. Its performance is closely related to the electrochemical properties of lithium-ion batteries. An ideal separator should have high electrolyte wettability and excellent electrochemical and thermal stability. At present, commercial separator materials are widely focused on polyolefin materials, such as polyethylene (PE) and polypropylene (PP), mainly due to the low cost, appropriate mechanical strength and good chemical and electrochemical stability of polyolefin materials. However, the thermal stability and electrolyte wettability of polyolefin materials are poor, which limits their wider application potential.
[0003] To address this problem, there are currently methods for modifying the material, among which surface coating modification is considered to be a relatively effective means of improving the electrolyte wetting and heat resistance of polyolefin separators. However, the current coating still has problems such as poor mechanical strength and weak bonding with the substrate. During the battery charge and discharge cycle and aging process, there is a risk of falling off from the substrate, which may lead to battery performance degradation.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In view of this, the embodiments of the present application provide a composite diaphragm and a preparation method thereof, a battery, and an electrical device to solve at least one problem existing in the background technology.
[0006] The first aspect of the present invention provides a composite membrane, comprising a base membrane layer and a functional modification layer disposed on at least one side of the base membrane layer; wherein:
[0007] The functional modified layer includes modified ceramics and modified sepiolite fibers; the modified ceramics include ceramic particles and polydopamine coated on the surfaces of the ceramic particles; the modified sepiolite fibers include sepiolite fibers and a silane coupling agent coated on the surfaces of the sepiolite fibers.
[0008] Preferably, the composite membrane satisfies at least one of the following characteristics (1) to (7):
[0009] (1) The base film is a polyolefin microporous film, and the polyolefin microporous film is selected from at least one of a polyethylene film, a polypropylene film, and a composite film of polyethylene and polypropylene;
[0010] (2) The ceramic particle material in the modified ceramic is selected from at least one of aluminum oxide, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, aluminum hydroxide, magnesium hydroxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP, LAGP, LLZO, and LCZP; the particle size of the modified ceramic is 100 nm to 3 μm;
[0011] (3) The silane coupling agent is at least one selected from vinyl triethoxysilane, vinyl trimethoxysilane, methacryloxy trimethoxysilane, methacryloxy triethoxysilane, acryl trimethoxy silane, and acryl triethoxy silane;
[0012] (4) In the modified sepiolite fiber, the length of the sepiolite fiber is 0.5 μm to 2 μm, and the diameter of the sepiolite fiber is 5 nm to 50 nm;
[0013] (5) The mass ratio of the modified ceramic to the modified sepiolite fiber is (10-17): (0.5-8);
[0014] (6) The thickness of the base film layer is 3 μm to 20 μm;
[0015] (7) The thickness of the modified functional layer is 0.5 μm to 5.5 μm.
[0016] The second aspect of the present invention provides a method for preparing the composite diaphragm according to the first aspect of the present invention, the preparation method comprising the following steps:
[0017] S1: preparing the modified ceramic: adding a modifier to a mixed solution of ethanol and Tris buffer to obtain a modifier solution, and adding ceramic particles to obtain the modified ceramic;
[0018] Preparation of the modified sepiolite fiber: adding a silane coupling agent to anhydrous ethanol, then adding sepiolite fiber to obtain a sepiolite fiber suspension, adjusting the pH, reacting, and obtaining the modified sepiolite fiber;
[0019] S2: adding the modified ceramic and modified sepiolite fiber obtained in step S1 to deionized water, and then adding an adhesive to obtain a suspension;
[0020] S3: adding a crosslinking agent and a catalyst to the suspension obtained in step S2 to obtain a functional modified layer slurry;
[0021] S4: coating the functional modification layer slurry obtained in step S3 on at least one surface of the base film layer to obtain the composite diaphragm.
[0022] Preferably, the step of preparing the modified ceramic satisfies at least one of the following features (1) to (3):
[0023] (1) The volume ratio of the ethanol to the Tris buffer is (0.5-2):1;
[0024] (2) The concentration of the modifier in the modifier solution is 2 mM to 15 mM, and the modifier is dopamine hydrochloride;
[0025] (3) After the step of adding ceramic particles, the method further includes the steps of stirring, filtering, washing and drying.
[0026] Preferably, the step of preparing the modified sepiolite fiber satisfies at least one of the following characteristics (1) to (4):
[0027] (1) In the sepiolite fiber suspension, the mass ratio of the silane coupling agent to the sepiolite fiber is (5-15):1; the sepiolite fiber accounts for 20%-40% of the total mass of the sepiolite fiber suspension;
[0028] (2) The pH is adjusted by using ammonia water, and the pH of the sepiolite fiber suspension after adjustment is 9 to 11;
[0029] (3) The reaction condition is heating, the heating temperature is 70° C. to 90° C., and the heating time is 2 h to 3 h;
[0030] (4) After the reaction, the method further comprises the steps of washing, filtering and drying.
[0031] Preferably, step S2 satisfies at least one of the following characteristics (1) to (5):
[0032] (1) The modified ceramic and modified sepiolite fibers account for 20% to 50% of the total mass of the suspension;
[0033] (2) Calculated based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 5% to 40%, the mass percentage of the modified ceramic is 50% to 90%, and the mass percentage of the adhesive is 3% to 10%;
[0034] (3) The adhesive is selected from a mixture or copolymer formed by one or more of polyvinyl alcohol, polymethyl methacrylate, polybutyl methacrylate, polyacrylonitrile, polyethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane, and urethane;
[0035] (4) The substance added simultaneously with the adhesive further comprises a thickener; the mass percentage of the thickener is 0.01% to 5% based on the total mass of the solid in the suspension being 100%; the thickener is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxypropyl methyl cellulose, sodium hydroxyethyl cellulose, sodium alginate, and guar gum;
[0036] (5) The substance added simultaneously with the adhesive also includes an auxiliary agent; based on the total mass of the solid in the suspension being 100%, the mass percentage of the auxiliary agent is 0.01% to 0.5%; the auxiliary agent is selected from at least one of fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, and fatty acid glyceride.
[0037] Preferably, in step S3, the cross-linking agent is selected from at least one of glutaraldehyde, formaldehyde, paraformaldehyde and epichlorohydrin, and the amount of the cross-linking agent added accounts for 5% to 20% of the total mass of the suspension;
[0038] Preferably, in step S3, the catalyst is selected from at least one of hydrochloric acid, oxalic acid and phosphoric acid, and the added amount of the catalyst accounts for 0.01% to 10% of the total mass of the suspension.
[0039] Preferably, in step S4, after the coating is completed, a drying step is further included, the drying temperature is 40° C. to 90° C., and the drying time is 10 min to 80 min;
[0040] Preferably, in step S4, the coating method is micro-gravure coating, extrusion coating, wire rod coating, dip coating or slot coating.
[0041] A third aspect of the present invention provides a battery, the battery comprising a diaphragm, the diaphragm being the composite diaphragm described in the first aspect of the present invention or the composite diaphragm prepared by the preparation method described in the second aspect of the present invention.
[0042] A fourth aspect of the present invention provides an electrical device, wherein the electrical device comprises the battery described in the third aspect of the present invention.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention provides a composite diaphragm and a preparation method thereof, a battery and an electrical device. The composite diaphragm not only has excellent heat resistance, but also has high mechanical strength, high peel strength and excellent ionic conductivity, and exhibits excellent cycle stability. The specific features are as follows:
[0045] (1) The functional modification layer of the composite diaphragm includes a ceramic material coated with polydopamine on the surface and a sepiolite fiber coated with a silane coupling agent on the surface. The surfaces of these two materials are rich in polar functional groups such as hydroxyl and amino groups, which effectively improve the wettability of the composite diaphragm to the electrolyte and the ionic conductivity.
[0046] (2) Ceramic particles, polydopamine, and sepiolite fibers all have excellent thermal stability, and their combined effect significantly improves the heat resistance of the composite diaphragm.
[0047] (3) In order to solve the problem that sepiolite fibers are easy to agglomerate due to their high surface energy, the present invention uses a silane coupling agent for modification, which effectively improves the dispersibility of sepiolite fibers and their compatibility and adhesion with polydopamine. Under the action of the cross-linking agent, a stable three-dimensional structure is formed between polydopamine, sepiolite fibers and adhesives, thereby greatly improving the puncture resistance of the diaphragm.
[0048] (4) There are abundant Lewis acid sites on the surface of sepiolite fibers, which can effectively fix anions in lithium salts (such as hexafluorophosphate anions) through acid-base interactions, promote the transmission of lithium ions, and facilitate the uniform deposition of lithium ions, thereby inhibiting the growth of lithium dendrites and significantly improving the cycle stability of the battery.
[0049] (5) In addition, the sepiolite fibers are rich in interconnected pore structures, which can effectively absorb HF and inhibit Fe 2+ The dissolution from the lithium iron phosphate cathode further improves the cycle stability of the battery. DETAILED DESCRIPTION
[0050] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0051] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0052] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0053] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0054] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0055] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0056] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0057] [Composite diaphragm]
[0058] A first aspect of the present invention provides a composite membrane, the composite membrane comprising a base membrane layer, and a functional modification layer disposed on at least one side surface of the base membrane layer;
[0059] The functional modified layer includes modified ceramics and modified sepiolite fibers; the modified ceramics include ceramic particles and polydopamine coated on the surface of the ceramic particles; the modified sepiolite fibers include sepiolite fibers and a silane coupling agent coated on the surface of the sepiolite fibers.
[0060] In the composite diaphragm provided by the present invention, the surfaces of the modified ceramic and modified sepiolite fibers are rich in polar functional groups such as hydroxyl and amino groups, which can effectively improve the composite diaphragm's ability to wet electrolytes and ionic conductivity; at the same time, the synergistic effect of ceramic particles, polydopamine and sepiolite fibers greatly improves the heat resistance of the diaphragm; in addition, there are abundant Lewis acid sites on the surface of sepiolite fibers, which can effectively fix hexafluorophosphate anions through acid-base interactions, promote the transmission of lithium ions, and facilitate the uniform deposition of lithium ions, thereby inhibiting the growth of lithium dendrites and significantly improving the cycle stability of the battery. The interconnected pore structure on the sepiolite fibers can effectively absorb HF and inhibit Fe 2+ The dissolution from the lithium iron phosphate cathode further improves the battery's cycle stability.
[0061] In certain embodiments, the base film is a polyolefin microporous film, and the polyolefin microporous film is selected from at least one of a polyethylene film, a polypropylene film, and a composite film of polyethylene and polypropylene.
[0062] In certain embodiments, the base film is a polyethylene microporous film.
[0063] In certain embodiments, the ceramic particle material in the modified ceramic is selected from at least one of aluminum oxide, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, aluminum hydroxide, magnesium hydroxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP, LAGP, LLZO, and LCZP.
[0064] In certain embodiments, the ceramic particle material in the modified ceramic is selected from alumina.
[0065] In some embodiments, the particle size of the modified ceramic is 100nm to 3μm, for example 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm or 3μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In certain embodiments, the silane coupling agent is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, methacryloxytrimethoxysilane, methacryloxytriethoxysilane, acryltrimethoxysilane, and acryltriethoxysilane.
[0067] In certain embodiments, the silane coupling agent is selected from vinyltriethoxysilane.
[0068] In some embodiments, in the modified sepiolite fiber, the length of the sepiolite fiber is 0.5 μm to 2 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In certain embodiments, in the modified sepiolite fiber, the diameter of the sepiolite fiber is 5 nm to 50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some embodiments, the mass ratio of the modified ceramic to the modified sepiolite fiber is (10-17): (0.5-8), for example, 10:0.5, 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 11:0.5, 11:1, 11:2, 11:3, 11:4, 11:5, 11:6, 11:7, 11:8, 12:0.5, 12:1, 12:2, 12:3, 12:4, 12:5, 12:7, 12:8, 13:0.5, 13:1, 13:2, 13:3, 13:4, : 13:5, 13:6, 13:7, 13:8, 14:0.5, 14:1, 14:2, 14:3, 14:4, 14:5, 14:6, 14:8, 15:0.1, 15:1, 15:2, 15:4, 15:6, 15:7, 15:8, 16:0.5, 16:1, 16:2, 16:3, 16:5, 16:6, 16:7, 17:0.5, 17:1, 17:2, 17:3, 17:4, 17:5, 17:6, 17:7 or 17:8, but not limited to the listed ratios, other ratios not listed within the ratio range are also applicable. Therefore, when the mass ratio of the modified ceramic to the modified sepiolite fiber is within this range, it can be ensured that the composite membrane has good heat resistance and excellent ionic conductivity.
[0071] In some embodiments, the thickness of the base film layer is 3μm to 20μm, for example 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In some embodiments, the thickness of the modified functional layer is 0.5 μm to 5.5 μm, for example 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or 5.5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] [Method for preparing composite diaphragm]
[0074] The second aspect of the present invention provides a method for preparing the composite diaphragm according to the first aspect of the present invention, the preparation method comprising the following steps:
[0075] S1: preparing the modified ceramic: adding a modifier to a mixed solution of ethanol and Tris buffer to obtain a modifier solution, and adding ceramic particles to obtain the modified ceramic;
[0076] Preparation of the modified sepiolite fiber: adding a silane coupling agent to anhydrous ethanol, then adding sepiolite fiber to obtain a sepiolite fiber suspension, adjusting the pH, reacting, and obtaining the modified sepiolite fiber;
[0077] S2: adding the modified ceramic and modified sepiolite fiber obtained in step S1 to deionized water, and then adding an adhesive to obtain a suspension;
[0078] S3: adding a crosslinking agent and a catalyst to the suspension obtained in step S2 to obtain a functional modified layer slurry;
[0079] S4: coating the functional modification layer slurry obtained in step S3 on at least one surface of the base film layer to obtain the composite diaphragm.
[0080] Under the action of the cross-linking agent, a stable three-dimensional structure is formed between polydopamine, sepiolite fibers and adhesives, thereby greatly improving the puncture resistance of the diaphragm.
[0081] In certain embodiments, in the step of preparing the modified ceramic, the volume ratio of the ethanol to the Tris buffer is (0.5-2):1.
[0082] In certain embodiments, in the step of preparing the modified ceramic, the concentration of the modifier in the modifier solution is 2 mM to 15 mM, for example 2 mM, 3 mM, 4 mM, 5 mM, 6 mM, 7 mM, 8 mM, 9 mM, 10 mM, 11 mM, 12 mM, 13 mM, 14 mM or 15 mM, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] In certain embodiments, in the step of preparing the modified ceramic, the modifier is dopamine hydrochloride.
[0084] In certain embodiments, in the step of preparing the modified ceramic, the mass ratio of the modifier to the ceramic particles is (5-15):1, such as 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable. Therefore, when the mass ratio of the modifier to the ceramic particles is within this range, it can ensure that the ceramic particles are completely coated with the modifier, and can also avoid the problem of insufficient coating of the modifier or the unstable polymer structure of the modifier falling off.
[0085] In some embodiments, in the step of preparing the modified ceramic, after the step of adding ceramic particles, the steps of stirring, filtering, washing and drying are further included; the stirring is mechanical stirring, and the stirring time is 10h to 14h, for example, 10h, 12h or 14h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the washing is cleaning with deionized water; the drying time is 10h to 14h, for example, 10h, 12h or 14h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the drying temperature is 50 to 70°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0086] In certain embodiments, in the step of preparing the modified sepiolite fiber, in the sepiolite fiber suspension, the mass ratio of the silane coupling agent to the sepiolite fiber is (5-15):1.
[0087] In certain embodiments, in the step of preparing the modified sepiolite fiber, in the sepiolite fiber suspension, the mass ratio of the silane coupling agent to the sepiolite fiber is (8-12):1, such as 8:1, 9:1, 10:1, 11:1 or 12:1, but is not limited to the listed ratios, and other ratios not listed within the ratio range are also applicable.
[0088] In the present application, as the amount of silane coupling agent (vinyl triethoxysilane) added changes, the dispersion and binding ability of sepiolite fibers in polydopamine-modified ceramics is enhanced, and the cross-linked network structure formed between the coating particles and fibers, and between the particles and fibers is more evenly distributed, which can improve the strength and ionic conductivity of the diaphragm; however, when the amount of silane coupling agent added is too high or too low, it will cause the coupling agent to self-polymerize and affect the dispersibility of sepiolite fibers, resulting in a decrease in the performance of the diaphragm and the electrochemical performance of the battery. However, when the amount of the silane coupling agent (vinyl triethoxysilane) added is within the above range, the resulting diaphragm has both high strength and excellent ionic conductivity, and the battery containing it also has excellent electrochemical performance.
[0089] In certain embodiments, in the step of preparing the modified sepiolite fiber, the sepiolite fiber accounts for 20% to 40% of the total mass of the sepiolite fiber suspension, for example 20%, 25%, 30%, 35% or 40%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] In certain embodiments, in the step of preparing the modified sepiolite fiber, the pH is adjusted using ammonia water, and the pH of the sepiolite fiber suspension after adjustment is 9 to 11, such as 9, 9.5, 10, 10.5 or 11, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] In certain embodiments, in the step of preparing the modified sepiolite fiber, the reaction condition is heating, and the heating temperature is 70°C to 90°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but are not limited to the listed values, and other values not listed within the numerical range are also applicable; the heating time is 2h to 3h, for example, 2h, 2.5h or 3h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0092] In certain embodiments, in the step of preparing the modified sepiolite fiber, the reaction further includes the steps of washing, filtering and drying; the washing is washing three times with anhydrous ethanol; the drying time is 10h to 14h, for example, 10h, 12h or 14h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the drying temperature is 70 to 90°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0093] In certain embodiments, in step S2, the modified ceramic and modified sepiolite fibers account for 20% to 50% of the total mass of the suspension, for example 20%, 25%, 30%, 35%, 40%, 45% or 50%, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0094] In certain embodiments, in step S2, based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 5% to 40%, the mass percentage of the modified ceramic is 50% to 90%, and the mass percentage of the adhesive is 3% to 10%.
[0095] In certain embodiments, in step S2, the adhesive is selected from a mixture or copolymer formed by one or more of polyvinyl alcohol, polymethyl methacrylate, polybutyl methacrylate, polyacrylonitrile, polyethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane, and urethane.
[0096] In certain embodiments, in step S2, the adhesive is selected from polyvinyl alcohol.
[0097] In certain embodiments, in step S2, the substance added simultaneously with the adhesive further includes a thickener; based on the total mass of solids in the suspension being 100%, the mass percentage of the thickener is 0.01% to 5%.
[0098] In certain embodiments, in step S2, the thickener is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxypropyl methyl cellulose, sodium hydroxyethyl cellulose, sodium alginate, and guar gum.
[0099] In certain embodiments, in step S2, the thickener is selected from sodium carboxymethyl cellulose.
[0100] In certain embodiments, in step S2, the substance added simultaneously with the adhesive further includes an auxiliary agent; based on the total mass of the solids in the suspension being 100%, the mass percentage of the auxiliary agent is 0.01% to 0.5%.
[0101] In certain embodiments, in step S2, the auxiliary agent is selected from at least one of fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium isethionate, sodium dodecylbenzene sulfonate, stearic acid, and fatty acid glyceride.
[0102] In certain embodiments, in step S2, the auxiliary agent is selected from fatty alcohol polyoxyethylene ether.
[0103] In certain embodiments, in step S2, after adding the adhesive, a stirring and dispersing step is further included, and the stirring and dispersing step is performed by using a stirrer.
[0104] In certain embodiments, step S2 is: adding the modified ceramic and modified sepiolite fiber obtained in step S1 to deionized water, and then adding an adhesive, a thickener and an auxiliary agent to obtain a suspension.
[0105] In certain embodiments, in step S2, based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 5% to 40%, the mass percentage of the modified ceramic is 50% to 90%, the mass percentage of the thickener is 0.01% to 5%, the mass percentage of the adhesive is 3% to 10%, and the mass percentage of the auxiliary agent is 0.01% to 0.5%.
[0106] In certain embodiments, in step S2, based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 20%, the mass percentage of the modified ceramic is 73.8%, the mass percentage of the thickener is 1%, the mass percentage of the adhesive is 5%, and the mass percentage of the auxiliary agent is 0.2%.
[0107] In certain embodiments, in step S2, based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 5%, the mass percentage of the modified ceramic is 88.8%, the mass percentage of the thickener is 1%, the mass percentage of the adhesive is 5%, and the mass percentage of the auxiliary agent is 0.2%.
[0108] In certain embodiments, in step S2, based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 40%, the mass percentage of the modified ceramic is 53.8%, the mass percentage of the thickener is 1%, the mass percentage of the adhesive is 5%, and the mass percentage of the auxiliary agent is 0.2%.
[0109] In certain embodiments, in step S3, the cross-linking agent is selected from at least one of glutaraldehyde, formaldehyde, paraformaldehyde, and epichlorohydrin.
[0110] In certain embodiments, in step S3, the cross-linking agent is selected from glutaraldehyde.
[0111] In certain embodiments, in step S3, the amount of the cross-linking agent added is 5% to 20% of the total mass of the suspension, for example 5%, 10%, 15% or 20%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0112] In certain embodiments, in step S3, the catalyst is selected from at least one of hydrochloric acid, oxalic acid, and phosphoric acid.
[0113] In certain embodiments, in step S3, the catalyst is selected from hydrochloric acid.
[0114] In certain embodiments, in step S3, the amount of the catalyst added is 0.01% to 10% of the total mass of the suspension, for example 0.1%, 0.5%, 1%, 1.5%, 2%, 3%, 5%, 7%, 10%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0115] In some embodiments, in step S4, after the coating is completed, a drying step is further included, and the drying temperature is 40°C to 90°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable; the drying time is 10min to 80min, for example, 10min, 20min, 30min, 40min, 50min, 60min, 70min or 80min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0116] In certain embodiments, in step S4, the coating method is micro-gravure coating, extrusion coating, wire rod coating, dip coating or slot coating.
[0117] In certain embodiments, in step S4, the coating method is wire rod coating.
[0118] [Battery]
[0119] A third aspect of the present invention provides a battery, comprising the composite diaphragm provided by the first aspect of the present invention or the composite diaphragm prepared by the preparation method provided by the second aspect of the present invention.
[0120] In some embodiments, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a lithium-ion battery, but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack lithium-ion battery, a square hard-shell battery, or a cylindrical hard-shell battery.
[0121] In some embodiments, the battery further comprises a positive electrode sheet, a negative electrode sheet and an electrolyte. Typically, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive / negative electrode from short-circuiting, while allowing ions to pass through.
[0122] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material suitable for the present invention may be various known positive electrode active materials that can be used for lithium ion batteries, which can reversibly embed and deintercalate lithium ions. The positive electrode active material may be selected from a composite oxide containing lithium and at least one selected from cobalt, manganese, nickel and iron, preferably a composite oxide containing lithium. The lithium-containing composite oxide is preferably LiM x O y and LiM x PO 4 One or more of, wherein M is a combination of one or more transition metals, 0<x≤3, 0<y≤4. Examples of positive electrode active materials include lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, lithium iron phosphate (LiFePO 4 ) etc. In some embodiments, the positive electrode active material includes NCM (811).
[0123] The positive electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of the conductive agent of the positive electrode include one or more of conductive carbon black, carbon fiber (CF), acetylene black, Ketjen black, graphene and carbon nanotubes. The binder of the positive electrode improves the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of the binder of the positive electrode include at least one of a fluorine-containing resin, a polypropylene resin, a fiber-type binder, a rubber-type binder and a polyimide-type binder. In some embodiments, the conductive agent in the positive electrode active material layer is conductive carbon black and single-walled carbon nanotubes, and the binder is polyvinylidene fluoride. The mass ratio of each component in the positive electrode active material layer can be conventional.
[0124] The positive electrode active material layer is obtained by coating a positive electrode slurry containing various components of the positive electrode active material layer and a solvent onto a positive electrode current collector, and then rolling and slitting. The solvent of the positive electrode slurry can be N-methylpyrrolidone (NMP).
[0125] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector may be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material may include a material capable of reversibly embedding / de-embedding lithium ions, lithium metal, lithium metal alloy, a material capable of doping / de-doping lithium, or a transition metal oxide. Examples of negative electrode active materials include lithium metal, structured lithium metal, graphite (e.g., natural graphite, artificial graphite), mesophase carbon spheres, hard carbon, soft carbon, silicon, silicon-oxygen materials (e.g., silicon dioxide, silicon oxide), silicon-carbon composite materials (Si / C composite materials), Li-Sn alloys, Li-Sn-O alloys, spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 , Li-Al alloy, etc. In some embodiments, the negative electrode active material comprises graphite.
[0126] The negative electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of negative electrode conductive agents include conductive carbon black, conductive graphite, vapor deposited carbon fiber (VGCF), carbon nanotubes, graphene, etc. The binder of the negative electrode improves the bonding performance between the negative electrode active material particles and between the negative electrode active material particles and the current collector. Examples of negative electrode binders include polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), cyclodextrin, gelatin, polyvinyl alcohol, polyacrylate, acrylonitrile multipolymer, etc. In some embodiments, the conductive agent in the negative electrode active material layer is acetylene black, and the binder is styrene butadiene rubber and sodium carboxymethyl cellulose. The mass ratio of each component in the negative electrode active material layer can be conventional.
[0127] The negative electrode active material layer is obtained by coating the negative electrode slurry containing the components of the negative electrode active material layer and a solvent onto the negative electrode current collector, and then rolling and slitting. The solvent of the negative electrode slurry can be a conventional solvent in the art, such as deionized water.
[0128] The electrolyte solution includes an organic solvent and an electrolyte salt.
[0129] Organic solvents suitable for the electrolyte of the present invention may include carbonate solvents, carboxylate solvents, ether solvents or other aprotic solvents. In some embodiments, the electrolyte includes carbonate solvents. In the electrolyte of the present invention, the mass of carbonate solvents can be 80% to 100% of the total mass of the organic solvent, such as 85%, 90%, 95%. Examples of carbonate solvents include ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, etc. In some embodiments, the organic solvent is selected from at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate. In some embodiments, the organic solvent comprises at least one cyclic carbonate and at least one linear carbonate. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, gamma-butyrolactone, etc. Examples of linear carbonates include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc.
[0130] The electrolyte salt may include or be selected from a lithium salt. The lithium salt may be selected from one or more of an organic lithium salt and an inorganic lithium salt. In some embodiments, the electrolyte salt is selected from LiPF 6 , LiBF 4 , LiFSI, LiTFSI, LiBOB, LiODFB and LiPO 2 F 2 In some embodiments, the concentration of the electrolyte salt in the electrolyte is 0.5 to 2 mol / L, such as 1 mol / L, 1.5 mol / L.
[0131] The battery of the present application also includes a packaging shell for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in lithium-ion batteries, and the present application does not limit the above-mentioned other components. The present application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of the present application.
[0132] The present invention has no special limitation on the method for preparing the battery, and the technical scheme for preparing the negative electrode material into a battery such as a secondary battery, which is well known to those skilled in the art, can be adopted.
[0133] It should be understood that since the battery provided in the present application includes the composite diaphragm provided in the first aspect of the present invention or the composite diaphragm prepared by the preparation method provided in the second aspect of the present invention, the beneficial effects of the composite diaphragm or the preparation method described in any of the above embodiments are applicable to the battery.
[0134] [Electrical devices]
[0135] A fourth aspect of the present invention provides an electrical device, comprising the battery provided by the third aspect of the present invention.
[0136] The use of the battery of the present application is not particularly limited, and it can be used for any electrical device known in the prior art. In some embodiments, the battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, drones, and lithium-ion capacitors, etc.
[0137] It should be understood that, since the electrical device provided in the present application includes the battery described in the third aspect of the present invention, the beneficial effects of the composite diaphragm described in any of the above embodiments are applicable to the electrical device.
[0138] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments.
[0139] Example 1
[0140] S101: preparing modified ceramics: ethanol and Tris buffer were mixed in a volume ratio of 1:1 to obtain a mixed solvent, dopamine was added and stirred for 12 hours to prepare a dopamine solution with a concentration of 8 mM, and then alumina (solid content of alumina in the solution was 10%) was added and mechanically stirred for 12 hours, and then the stirred material was washed with deionized water, and placed in a vacuum oven at 60° C. for 12 hours to obtain modified alumina (i.e., modified ceramics);
[0141] Preparation of modified sepiolite fiber: Disperse vinyl triethoxysilane in anhydrous ethanol, stir for 30 minutes to prepare a solution with a concentration of 10%, then add sepiolite fiber (the mass ratio of vinyl triethoxysilane to sepiolite fiber is 10:1) and stir and disperse to obtain a sepiolite fiber suspension with a concentration of 30%, and add ammonia water to adjust the pH to 10. Then heat the sepiolite fiber suspension to 80°C and react for 2.5 hours, wash the powder with anhydrous ethanol and filter it three times, and then dry it at 80°C for 12 hours to obtain modified sepiolite fiber.
[0142] S102: Add the modified aluminum fluoride obtained in step S101 and the modified sepiolite fiber obtained in step S101 to deionized water, mix them by mechanical stirring to form a suspension with a concentration of 40%, then add a thickener (sodium carboxymethyl cellulose), an adhesive (polyvinyl alcohol) and an auxiliary agent (fatty alcohol polyoxyethylene ether), and use a high-speed disperser to form a 35% suspension. Among the solid content of the suspension, the mass proportion of modified aluminum oxide is 73.8%, the mass proportion of modified sepiolite fiber is 20%, the mass proportion of adhesive is 5%, the mass proportion of sodium carboxymethyl cellulose is 1%, and the mass proportion of auxiliary agent is 0.2%.
[0143] S103: Add a crosslinking agent (glutaraldehyde) and a catalyst (hydrochloric acid) to the suspension obtained in step S102, and stir and mix to obtain a coating solution (i.e., functional modification layer slurry). The amount of glutaraldehyde added is 10% by mass of the suspension, and the amount of hydrochloric acid added is 0.5% by mass of the suspension.
[0144] S104: Use wire rod coating to apply the coating solution obtained in step S103 to one side of a polyethylene-based film with a thickness of 7 μm, and bake at 60° C. for 60 minutes to obtain a composite diaphragm. The thickness of the functional modification layer measured by a micrometer is 3 μm.
[0145] Example 2
[0146] The only difference between Example 2 and Example 1 is that in step S101, the mass ratio of vinyl triethoxy silane to sepiolite fiber is 5:1.
[0147] Example 3
[0148] The only difference between Example 3 and Example 1 is that in step S101, the mass ratio of vinyl triethoxy silane to sepiolite fiber is 15:1.
[0149] Example 4
[0150] The only difference between Example 4 and Example 1 is that in step S101, the concentration of the prepared dopamine solution is 2 mM.
[0151] Example 5
[0152] The only difference between Example 5 and Example 1 is that in step S101, the concentration of the prepared dopamine solution is 15 mM.
[0153] Example 6
[0154] The only difference between Example 6 and Example 1 is that in step S102, the mass proportion of modified alumina in the solid content of the suspension is 88.8%, and the mass proportion of modified sepiolite is 5%.
[0155] Example 7
[0156] The only difference between Example 7 and Example 1 is that in step S102, the mass proportion of modified alumina in the solid content of the suspension is 53.8%, and the mass proportion of modified sepiolite is 40%.
[0157] Comparative Example 1
[0158] The only difference between Comparative Example 1 and Example 1 is that in step S102, the modified alumina accounts for 93.8% of the solid content of the suspension, and no modified sepiolite fiber is added.
[0159] Comparative Example 2
[0160] The only difference between Comparative Example 2 and Example 1 is that in step S102, the modified alumina is replaced by unmodified alumina; the mass proportion of unmodified alumina in the solid content of the suspension is 93.8%, and no modified sepiolite fiber is added.
[0161] Diaphragm performance test
[0162] The membrane performance tests were conducted on the membranes obtained in Examples 1 to 7 and Comparative Examples 1 to 2, and the test results are shown in Table 1. The test items were needle puncture strength, peel strength, thermal shrinkage and ionic conductivity.
[0163] - Needle puncture strength, thermal shrinkage and ionic conductivity tests: The tests are carried out in accordance with the national standard GB / T 36363 2018 "Polyolefin separators for lithium-ion batteries";
[0164] -Peel strength test: Cut the diaphragm into 25mm*200mm strips, stick the coating surface to the surface of 3M tape, and use a universal tensile testing machine to test at a rate of 50mm / min.
[0165] Electrochemical performance test
[0166] Preparation of lithium-ion batteries:
[0167] (1) Positive electrode sheet: First, the positive electrode active material (LFP), PVDF and polyphosphate dispersant are mixed in a mass ratio of 97.88:2:0.12, and the solvent N-methylpyrrolidone is added. After stirring until the system is uniform under the action of a vacuum mixer, it is coated on the surface of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying. The positive electrode sheet is then obtained by cold pressing and slitting.
[0168] (2) Negative electrode sheet: First, artificial graphite, conductive carbon black (Super P), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 96.5:1:1:1.5, and deionized water is added as a solvent. After stirring until the system becomes uniform under the action of a vacuum mixer, it is coated on the surface of the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying. Then, the negative electrode sheet is obtained by cold pressing and slitting.
[0169] (3) Electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate were mixed in a volume ratio of 1:1:1 as a solvent, and LiPF 6 Prepared into electrolyte. LiPF in the electrolyte 6 The concentration is 1 mol / L.
[0170] (4) Diaphragm: The composite diaphragms obtained in Examples 1 to 7 and Comparative Examples 1 to 2 were used as diaphragms.
[0171] (5) Assembly: The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, then wound into a battery cell and loaded into an aluminum shell. After liquid injection, packaging, formation and other processes, a 5Ah soft-pack battery is obtained.
[0172] The batteries including the separators of Examples 1 to 7 or Comparative Examples 1 to 2 were respectively tested for 1C / 1C cycle 1000-cycle capacity retention rate: using a blue battery test system, at 25°C, 1C rate constant current discharge to 2.0V, then 1C current constant current charge to 3.65V, then constant voltage 3.65V charge until the current reaches 0.05C cut-off, record the charging capacity at this time as the first cycle charging capacity, this is one cycle; repeat the process test for 1000 cycles, record the charging capacity of the 1000th cycle, capacity retention rate = 1000th cycle charging capacity / first cycle charging capacity * 100%. The test results are shown in Table 1.
[0173] Table 1
[0174]
[0175] It can be seen from Table 1 that, relative to Comparative Example 2, the composite separators prepared in Examples 1-7 all have excellent mechanical strength and heat resistance, ionic conductivity, and adhesion between the ceramic coating and the substrate, and the assembled lithium-ion batteries also have better cyclability.
[0176] Compared with Example 1, the strength, heat resistance, ion conductivity and cycle performance of the composite diaphragms of Example 2 and Example 3 are all reduced, indicating that with the change in the amount of silane coupling agent (vinyl triethoxysilane) added, the dispersion and binding ability of sepiolite fibers in polydopamine-modified ceramics is enhanced, and the cross-linked network structure formed between the coating particles and fibers, and between particles and fibers is more evenly distributed, which can improve the strength and ion conductivity of the diaphragm. When the amount of silane coupling agent added is too high or too low, it will cause the coupling agent to self-polymerize and affect the dispersibility of sepiolite fibers, resulting in a decrease in the performance of the diaphragm and the electrochemical performance of the battery.
[0177] By comparing Example 1, Example 4, and Example 5, it can be found that the content of polydopamine coated on the ceramic surface will affect the ionic conductivity of the diaphragm, the bonding strength with the substrate, the heat resistance, and the cycle performance of the battery.
[0178] By comparing Example 1, Example 6, and Example 7, it can be found that the strength difference of the diaphragm is not much; but when the sepiolite fiber content is too high, the heat resistance of the diaphragm decreases significantly; and as the sepiolite fiber content increases, the ionic conductivity of the diaphragm and the battery cycle performance increase accordingly.
[0179] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base membrane layer and a functional modification layer disposed on at least one side of the base membrane layer; wherein, The functional modified layer includes modified ceramics and modified sepiolite fibers; the modified ceramics include ceramic particles and polydopamine coated on the surfaces of the ceramic particles; the modified sepiolite fibers include sepiolite fibers and a silane coupling agent coated on the surfaces of the sepiolite fibers.
2. The composite diaphragm according to claim 1, characterized in that: The composite diaphragm satisfies at least one of the following characteristics (1) to (7): (1) The base film is a polyolefin microporous film, and the polyolefin microporous film is selected from at least one of a polyethylene film, a polypropylene film, and a composite film of polyethylene and polypropylene; (2) The ceramic particle material in the modified ceramic is selected from at least one of aluminum oxide, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, aluminum hydroxide, magnesium hydroxide, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP, LAGP, LLZO, and LCZP; the particle size of the modified ceramic is 100 nm to 3 μm; (3) The silane coupling agent is at least one selected from vinyl triethoxysilane, vinyl trimethoxysilane, methacryloxy trimethoxysilane, methacryloxy triethoxysilane, acryl trimethoxy silane, and acryl triethoxy silane; (4) In the modified sepiolite fiber, the length of the sepiolite fiber is 0.5 μm to 2 μm, and the diameter of the sepiolite fiber is 5 nm to 50 nm; (5) The mass ratio of the modified ceramic to the modified sepiolite fiber is (10-17): (0.5-8); (6) The thickness of the base film layer is 3 μm to 20 μm; (7) The thickness of the modified functional layer is 0.5 μm to 5.5 μm.
3. A method for preparing a composite diaphragm according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: preparing the modified ceramic: adding a modifier to a mixed solution of ethanol and Tris buffer to obtain a modifier solution, and adding ceramic particles to obtain the modified ceramic; Preparation of the modified sepiolite fiber: adding a silane coupling agent to anhydrous ethanol, then adding sepiolite fiber to obtain a sepiolite fiber suspension, adjusting the pH, reacting, and obtaining the modified sepiolite fiber; S2: adding the modified ceramic and modified sepiolite fiber obtained in step S1 to deionized water, and then adding an adhesive to obtain a suspension; S3: adding a crosslinking agent and a catalyst to the suspension obtained in step S2 to obtain a functional modified layer slurry; S4: coating the functional modification layer slurry obtained in step S3 on at least one surface of the base film layer to obtain the composite diaphragm.
4. The method for preparing the composite diaphragm according to claim 3, characterized in that: The step of preparing the modified ceramic satisfies at least one of the following features (1) to (3): (1) The volume ratio of the ethanol to the Tris buffer is (0.5-2):1; (2) The concentration of the modifier in the modifier solution is 2 mM to 15 mM, and the modifier is dopamine hydrochloride; (3) After the step of adding ceramic particles, the method further includes the steps of stirring, filtering, washing and drying.
5. The method for preparing the composite diaphragm according to claim 3, characterized in that: The step of preparing the modified sepiolite fiber satisfies at least one of the following characteristics (1) to (4): (1) In the sepiolite fiber suspension, the mass ratio of the silane coupling agent to the sepiolite fiber is (5-15):1; the sepiolite fiber accounts for 20%-40% of the total mass of the sepiolite fiber suspension; (2) The pH is adjusted by using ammonia water, and the pH of the sepiolite fiber suspension after adjustment is 9 to 11; (3) The reaction condition is heating, the heating temperature is 70° C. to 90° C., and the heating time is 2 h to 3 h; (4) After the reaction, the method further comprises the steps of washing, filtering and drying.
6. The method for preparing a composite diaphragm according to claim 3, characterized in that: Step S2 satisfies at least one of the following characteristics (1) to (5): (1) The modified ceramic and modified sepiolite fibers account for 20% to 50% of the total mass of the suspension; (2) Calculated based on the total mass of solids in the suspension being 100%, the mass percentage of the modified sepiolite fiber is 5% to 40%, the mass percentage of the modified ceramic is 50% to 90%, and the mass percentage of the adhesive is 3% to 10%; (3) The adhesive is selected from a mixture or copolymer formed by one or more of polyvinyl alcohol, polymethyl methacrylate, polybutyl methacrylate, polyacrylonitrile, polyethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane, and urethane; (4) The substance added simultaneously with the adhesive further comprises a thickener; the mass percentage of the thickener is 0.01% to 5% based on the total mass of the solid in the suspension being 100%; the thickener is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxypropyl methyl cellulose, sodium hydroxyethyl cellulose, sodium alginate, and guar gum; (5) The substance added simultaneously with the adhesive also includes an auxiliary agent; based on the total mass of the solid in the suspension being 100%, the mass percentage of the auxiliary agent is 0.01% to 0.5%; the auxiliary agent is selected from at least one of fatty alcohol polyoxyethylene ether, sodium butylbenzene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, and fatty acid glyceride.
7. The method for preparing a composite diaphragm according to claim 3, characterized in that: In step S3, the cross-linking agent is selected from at least one of glutaraldehyde, formaldehyde, paraformaldehyde and epichlorohydrin, and the amount of the cross-linking agent added accounts for 5% to 20% of the total mass of the suspension; The catalyst is selected from at least one of hydrochloric acid, oxalic acid and phosphoric acid, and the added amount of the catalyst accounts for 0.01% to 10% of the total mass of the suspension.
8. The method for preparing a composite diaphragm according to claim 3, characterized in that: In step S4, after the coating is completed, a drying step is also included, the drying temperature is 40° C. to 90° C., and the drying time is 10 min to 80 min; The coating method is micro-gravure coating, extrusion coating, wire rod coating, dip coating or slot coating.
9. A battery, characterized in that: The battery comprises a diaphragm, and the diaphragm is the composite diaphragm according to claim 1 or 2 or a composite diaphragm prepared by the preparation method according to any one of claims 3-8.
10. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 9.
Citation Information
Patent Citations
Composite ceramic diaphragm and application thereof
CN106601967A
Ceramic diaphragm with dopamine-containing composite binder and application of ceramic diaphragm with dopamine-containing composite binder in lithium ion battery
CN107507950A
Method for improving performance of lithium ion battery diaphragm
CN118531559A
Integrated preparation method of composite lithium battery diaphragm
CN119092936A
Separator for battery and battery using the same
JP2005276503A
Cited By
Composite diaphragm, preparation method thereof and battery
CN121394775A